The Normativity of Work: Retrieving a Critical Craft Norm. Issue 1 (2nd January 2017) - Tweedie, Dale
ABSTRACT: Recent social theory has begun to reconsider how the activity of work can contribute to well-being or autonomy under the right conditions. However, there is no consensus on what this contribution consists in, and so on precisely which normative principles should be marshalled to critique harmful or repressive forms of workplace organisation. This paper argues that Richard Sennett's concept of work as craft provides a normative standard against which the organisation of work can be assessed, especially when explained within a broadly Aristotelian account of the conditions of human flourishing. More precisely, the paper argues that a craft norm can meet the standards of social critique within the Frankfurt School tradition of Critical Theory, as this tradition has been interpreted by Axel Honneth. Honneth himself now rejects craft norms as too utopian and parochial to inform Critical Theory under contemporary economic conditions. In reply, this paper uses sociological studies of call centre workers to illustrate how work motivated by craft ideals can be sustainable rather than utopian, and how craftsmanship can inform social critique across a wide variety of industries and management practices.